Pemanfaatan Instagram “Teladan Rasul” dalam Pemenuhan Informasi Keagamaan Dikalangan Remaja Kota Kisaran Kabupaten Asahan - Husnah, Ade Humairoh (Lembaga Yasin AlSys, 2023)
This research in the form of a thesis aims to find out and understand the Rasul's Instagram example, including a forum for adding religious information among teenagers and to find out what the positive impact of the Rasul's Instagram example is being used by today's teenagers to fulfill the need for religious information through Instagram social media, especially teenagers in the city. Kisaran, Asahan Regency.The research method used is a qualitative research method, using a communication sociology approach, while data collection techniques are carried out by means of observation, interviews and documentation.The results of the research show that Rasul's exemplary Instagram is a forum for fulfilling the religious information needs of City Teenagers. The range of information obtained from Rasul's exemplary account is in the form of photos and videos with a short duration but the information obtained is accurate so that what is conveyed is in accordance with religious information needs for teenagers and received a good response among Kisaran City teenagers. Likewise, the positive impact of Rasul's Instagram example on the lives of teenagers in Kisaran City in their daily lives, such as a lot of knowledge and knowledge about the Islamic religion, which at first they didn't know about, became more knowledgeable. There is a desire to improve themselves after reading the messages in the Rasul's exemplary account so that teenagers become interested in preaching to millennial teenagers as was done in the Rasul's exemplary account.